Pediatric Carbon Monoxide Poisoning in Southern Israel: A Cross-Sectional Study. Issue 11 (November 2020) - Fruchtman, Yariv; Perry, Zvi H.; Leibson, Tom; Vered Cohen, Liat; Lifshitz, Matitiahu; Leibovitz, Eugene
Abstract : Objectives: This study aimed to describe the epidemiology and clinical burden of unintended carbon monoxide (CO) poisoning among children in the Negev region of southern Israel. Methods: This was a cross-sectional retrospective study of CO poisoning patients admitted to Soroka University Medical Center in 2011 through 2015. Results: Overall, 43 cases of CO poisoning were recorded among children younger than 18 years. Five patients died, all upon admission. Poisoning due to smoke "per se" and due to CO emitted from heating devices were responsible for 28 (65.1%) and 14 (32.6%) cases, respectively. Eight (18.6%) patients suffered from convulsions, and 13 (43.3%) of 30 evaluable patients complained of headaches. Twenty-two (51.2%) were found unconscious in the field, and 7 (16.3%) were unconscious at examination at the emergency department. The average carboxyhemoglobin level on admission was 10.5% ± 10.4% (level ranging from 0.1% to 46.2%). Treatment included oxygen in 34 patients (79%) and hyperbaric oxygen therapy in 8 patients (19%). No differences were found between Bedouin and Jewish children in sex, age, residence area, source of CO poisoning, symptoms severity, and need for hyperbaric oxygen therapy. More patients with exposure to water heating devices were older than 4 years, lived in villages, and were diagnosed as having loss of consciousness in the field compared with those exposed to smoke inhalation. Conclusions: Carbon monoxide poisoning in children is frequent in southern Israel. Education about prevention, implementation of safer standards for home heating systems, and government supervision are required management strategies to decrease the CO poisoning incidence in southern Israel.